Quantitative evaluation of explosion consequences in urban underground drainage. (May 2021) - Li, Yuanzhi; Qian, Xinming; Yuan, Mengqi; Hou, Longfei; Wu, Yawei; Duanmu, Weike; Chen, Jun
Highlights: A method to quantitatively evaluate underdrain explosion consequences was established. Damage effects of explosion fragments, overpressure, and vibration are calculated. Social impact and emergency rescue capability were assessed and discussed. Underdrain explosion experiment was conducted to restore the Qingdao accident. The model was validated by generating a case study to assess explosion consequences. Abstract: The leaked gas from urban pipelines can easily spread to adjacent underground spaces and cause dangerous explosion accidents, therefore it is crucial to accurately identify underground spaces with high explosion consequences quantitatively, which is the key link to carry out the underground space explosion risk assessment. This paper proposes a method to quantitatively estimate the consequences of the urban underground drainage explosions. The method is established based on a large-scale underground explosion experiment and consists of several damage indicators as well as correction factors. The effects of fragments after the gas explosion, overpressure, and ground vibration post-explosion on nearby residents, infrastructures, and buried pipelines are quantitatively investigated through experimental results and theoretical analysis. The social impact and rescue force distribution affected by the explosion are assessed. A case study was generated in urban area which showed that this method is practicable. The results presented here may provide sound theoretical guidance for urban pipeline risk assessment and explosion hazard control.